The Role of AI in Personalizing Insurance Policies - Ramesh Pingili (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article analyzes the transformative impact of artificial intelligence on the insurance industry through four key innovations. It examines how AI has enabled real-time risk assessment and dynamic pricing through personalized policy optimization, integrated terabytes of daily customer data for precise underwriting, implemented advanced analytics frameworks for enhanced fraud detection and customer segmentation, and automated operations for improved efficiency. The findings demonstrate that AI implementation has achieved an 82% improvement in risk prediction accuracy, reduced operational costs by 67%, and increased customer satisfaction by 76%. However, these technological advancements necessitate robust ethical governance frameworks, particularly in data privacy and algorithmic fairness. The research comprehensively analyzes AI’s role in reshaping insurance operations while emphasizing the critical balance between technological innovation and ethical implementation. These insights offer valuable guidance for insurance providers pursuing digital transformation while maintaining regulatory compliance and customer trust.